Metode Muraja'ah Hafalan Al-Qur'an di Madrasah Ibtidaiyah At Tamimi - Maemunah Maemunah (JIECO: Journal of Islamic Education Counseling, 2021)
ABSTRACT The background of this research is based on preliminary research on several Islamic Madrasahs in Garut Regency, it shows that the method of memorizing the Qur'an is not optimal because it is not optimal in planning, implementing and evaluating so that it has a negative impact on students' memorization. The purpose of this study was to obtain an overview of the planning, implementation, evaluation, problems and solutions of the Al-Qur'an muraja'ah memorization method in Madrasah Ibtidaiyah At Tamimi, Garut Regency. Qs theological foundation. Al-An'am: 105 and Qs. Al-Qamar: 17. The philosophical foundation uses the philosophy of constructivism, the theoretical foundation uses the principle of repetition in learning. This study used a qualitative approach, case study methods and data collection techniques were carried out through triangulation of observations, interviews and documentation studies. Meanwhile, the data source was through triangulation: madrasah principals, teachers and students. The results showed: First, in the planning aspects of the Al-Qur'an recitation of the muraja'ah method in Madrasah Ibtidaiyah, it involved various parties, namely foundations, committees, madrasah principals and teacher councils which included setting goals, determining materials, activities and evaluation tools to be used. Second, in the implementation aspect of the muraja'ah memorization method of Al-Qur'an, it consists of three activities, namely introduction, core and closing. In the core activities of the implementation, it involves supervisors and peers, namely muraja'ah memorization together being guided and listened to by the teacher, muraja'ah memorization listened to by peers and muraja'ah memorization, each listened to by the teacher. Third, in the aspect of evaluating muraja'ah memorizing Al-Qur'an, there are two types, namely evaluation of learning outcomes which are carried out every week, mid-semester, end of semester and end of graduation. Process evaluation is carried out in the following school year. Fourth, the problems faced in the method of memorizing the Al-Qur'an muraja'ah consist of student factors, namely the level of age maturity, differences in ability levels and lack of willingness or motivation to memorize, in terms of educators, namely the lack of teacher competence and environmental factors, namely family. and playmates. Fifth, the solution in dealing with the problem is to increase teacher competence, create a pleasant learning atmosphere, according to the age and character of students so that children are focused and motivated and are not affected by the surrounding environment. In addition, collaborating with parents of students and Koran teachers in their respective regions. Keywords: muraja'ah method, memorizing Al-Qur'an